2019
DOI: 10.1177/1474704919870990
|View full text |Cite
|
Sign up to set email alerts
|

Disgust Proneness and Personal Space in Children

Abstract: Individuals vary in their personal space (PS) size as reflected by the preferred distance to another person during social interactions. A previous study with adults showed that pathogen-relevant disgust proneness (DP) predicted PS magnitude. The present study investigated whether this association between DP and PS already exists in 8- to 12-year-old children (144 girls, 101 boys). The children answered a disgust questionnaire with the two trait dimensions “core disgust (contact with spoiled food and poor hygie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…In this situation, the participant may have perceived the experimenter as a reliable stranger, and this perception may have led to a decrease in his perception of danger, as stated in Lough's study [17]. Since children's perception of adult strangers as more threatening may lead to different results, the results to be collected from children with hearing loss will be valuable [7].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In this situation, the participant may have perceived the experimenter as a reliable stranger, and this perception may have led to a decrease in his perception of danger, as stated in Lough's study [17]. Since children's perception of adult strangers as more threatening may lead to different results, the results to be collected from children with hearing loss will be valuable [7].…”
Section: Discussionmentioning
confidence: 98%
“…Most people value their personal space and feel discomfort, anger, or anxiety when their personal space is violated [6]. When defining personal space, characteristics such as age, gender, mood, and facial expression of the approaching person may affect the preferred interpersonal distance [7]. For example, it has been found that younger individuals prefer closer interpersonal distances than older individuals [4].…”
Section: Introductionmentioning
confidence: 99%
“…In Study 1, a group of adults was surveyed about the items they and their children find disgusting. As we noted above, prior measures of disgust sensitivity for children were adapted from adult measures (Muris et al, 2012; Nadeau et al, 2017; Schienle & Schwab, 2019; Viar-Paxton et al, 2015), and theories of a mature theory of disgust focus on abstract concepts, rather than sensory properties (Rozin & Fallon, 1987; for a review, see Rottman et al, 2019). As such, these measures tend to omit questions about uncontaminated foods when examining disgust sensitivity.…”
Section: Study 1: Online Parent Surveymentioning
confidence: 99%
“…The developmental antecedents of disgust (observed in children) are often considered to be immature steps preceding the adult state. For example, rather than eliciting responses from children regarding what they find to be disgusting, disgust sensitivity scales for children have typically been directly adapted from existing adult scales (Muris et al, 2012; Nadeau et al, 2017; Schienle & Schwab, 2019; Viar-Paxton et al, 2015), but without items that might be inappropriate for young children (e.g., those dealing with sexual behavior). In addition, theories of the development of disgust have often focused on the transition from concrete to abstract thinking (for a review, see Rottman et al, 2019).…”
mentioning
confidence: 99%